Effectiveness of interventions for the development of leadership skills among nurses: a systematic review protocol. (June 2016) - Darragh, Michael; Traynor, Victoria; Joyce-McCoach, Joanne
Abstract : Review question/objective: What interventions are the most effective for the development of leadership skills for nurses? The review objective is to systematically review the evidence to identify the effectiveness of interventions for the development of leadership skills among nurses. Center conducting the review: Centre for Evidence-based Initiatives in Health Care – University of Wollongong: an Affiliate Center of the Joanna Briggs Institute.